Analisis Biaya dan Waktu dengan Menggunakan Metode Nilai Hasil (Earned Value) pada Proyek Pembangunan Mako Polres Jakarta Barat - Arthono, Andri; Rahayu, Diana; Purbakawaca, Rady (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
In carrying out a construction project, the project should be a solid building and have a long life. Criteria and characteristics of a good building of course. It should be realized that changes may occur in the future and will affect the pattern of the plan it self. The length of time for project completion has a major impact on the increase in overall project costs. has been completed or implemented When viewed from the amount of work completed, the concept of Earned Value is one of the control methods used to control project costs and time in an integrated manner. This method is used to analyze implementation performance and make project completion estimates that provide information on project performance in a reporting period and produce cost and time estimates for the completion of all project work. This project is planned for 204 days or about 29 weeks with a contract value of Rp. 106,671,014,961.00